Anthropometric Characteristics of Elite Soccer Players from Bosnia and Herzegovina and Montenegro - Marin Corluka; Dusko Bjelica; Jovan Gardasevic; Ivan Vasiljevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The aim of this research was to determine the differences among the top soccer players of the club in Bosnia and Herzegovina, CSC Zrinjski Mostar and the top soccer players of the club in Montenegro FC Buducnost, the champions in their countries, in the anthropometric characteristics and body composition. A sample of 58 subjects was divided into two sub-samples. The first sub-sample of the subjects consisted of 28 soccer players of CSC Zrinjski Mostar of the average age 24.36±4.14, the champions of the Bosnia and Herzegovina in the season 2016/17, while the other sub-sample consisted of 30 soccer players of FC Buducnost of the average age 22.73±4.33, the champions of the Montenegro Championship in the season 2016/17. Soccer players were tested immediately after the end of the competition season 2016/17. Anthropometric characteristics in the body composition were evaluated by a battery of 10 variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold, body mass index, fat percentage and muscle mass. The standard central and dispersion parameters of all variables were calculated. The significance of the differences between the players of the top two soccer clubs in the Anthropometric characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was found that the soccer players of the two mentioned clubs have statistically significant differences by the three variables that estimate the waist circumference, biceps skinfold and abdominal skinfold, in a favor of CSC Zrinjski Mostar.